Mental health intervention to address climate anxiety in adolescents: a systematic review - Cahyani, Kadek Dewi; Sari, Indah Permata; Permatasari, Henny; Mulyono, Sigit; Basrowi, Ray Wagiu; Nafilata, Ikrimah (Universitas Gadjah Mada, 2025)
Purpose: This study aims to identify and analyze interventions implemented to address the impact of climate change on adolescents' mental health. Methods: This systematic review was conducted using PRISMA guidelines. A literature search was conducted across four primary databases — PubMed, ScienceDirect, EBSCO, and Scopus —with keywords related to interventions, climate change, and adolescent mental health. Inclusion criteria include studies involving adolescents aged 10-18 years and featuring an original research design published within the last five years. Of the 1,579 studies identified, 22 articles were assessed for eligibility, and seven underwent quantitative synthesis. Results: Suggest that effective environmental education interventions can increase understanding and reduce anxiety among adolescents. Conclusion: To address the impacts of mental health on adolescents, interventions such as pro-environmental interventions, education, and augmented reality can be employed.